2004
DOI: 10.1159/000082369
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Syndrome Associated with Lumbar Spinal Stenosis

Abstract: Lumbar spinal stenosis is well defined in patho-anatomical terms but its clinical features are heterogeneous. We carried out a comprehensive retrospective review of the clinical features, radiological changes and outcome of 75 patients with radiologically diagnosed lumbar spinal stenosis in order to define its clinical spectrum. The presenting complaints were of weakness, numbness/tingling, radicular pain and neurogenic claudication in almost equal proportions. The commonest symptom was numbness or tingling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 32 publications
6
43
0
6
Order By: Relevance
“…In fact, 65.0% (26 of 40 patients) of patients with preoperative resting numbness still showed residual leg pain/numbness 2 years after the operation (Table 2). Numbness caused by LSS has been reported to be more difficult to alleviate by surgery than other neurological symptoms such as muscle weakness or pain [2,6]. Also, it is not surprising that preoperative drop foot eventually leads to postoperative gait disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 65.0% (26 of 40 patients) of patients with preoperative resting numbness still showed residual leg pain/numbness 2 years after the operation (Table 2). Numbness caused by LSS has been reported to be more difficult to alleviate by surgery than other neurological symptoms such as muscle weakness or pain [2,6]. Also, it is not surprising that preoperative drop foot eventually leads to postoperative gait disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Typical presenting complaints include weakness, numbness/tingling, radicular pain and neurogenic claudication, sometimes accompanied by pain in the lower back or buttocks [17,55]. The consequence, in addition to much discomfort, is a restriction in mobility, and this, coupled with the natural age-associated decline in musculoskeletal function, results in a serious impediment to the performance of activities of daily living and a threat to the patient's independence.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, limb numbness is one of the main symptoms in LSS patients. Goh et al [11] investigated the clinical symptoms associated with LSS and reported that 66.6% of the patients experienced numbness or tingling of the legs. Since numbness is usually associated with a feeling of muscular weakness in most of LSS patients, the VAS for numbness may also reflect a subjective assessment of the severity of motor weakness in the lower limbs.…”
Section: Discussionmentioning
confidence: 99%